Excess processing of oxidative damaged bases causes hypersensitivity to oxidative stress and low dose rate irradiation. (October 2015) - Yoshikawa, Y.; Yamasaki, A.; Takatori, K.; Suzuki, M.; Kobayashi, J.; Takao, M.; Zhang-Akiyama, Q.-M.
Abstract Ionizing radiations such as X-ray and γ-ray can directly or indirectly produce clustered or multiple damages in DNA. Previous studies have reported that overexpression of DNA glycosylases in Escherichia coli (E. coli) and human lymphoblast cells caused increased sensitivity to γ-ray and X-ray irradiation. However, the effects and the mechanisms of other radiation, such as low dose rate radiation, heavy-ion beams, or hydrogen peroxide (H2O2), are still poorly understood. In the present study, we constructed a stable HeLaS3 cell line overexpressing human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) protein. We determined the survival of HeLaS3 and HeLaS3/hOGG1 cells exposed to UV, heavy-ion beams, γ-rays, and H2O2. The results showed that HeLaS3 cells overexpressing hOGG1 were more sensitive to γ-rays, OH, and H2O2, but not to UV or heavy-ion beams, than control HeLaS3. We further determined the levels of 8-oxoG foci and of chromosomal double-strand breaks (DSBs) by detecting γ-H2AX foci formation in DNA. The results demonstrated that both γ-rays and H2O2 induced 8-oxoguanine (8-oxoG) foci formation in HeLaS3 cells. hOGG1-overexpressing cells had increased amounts of γ-H2AX foci and decreased amounts of 8-oxoG foci compared with HeLaS3 control cells. These results suggest that excess hOGG1 removes the oxidatively damaged 8-oxoG in DNA more efficiently and therefore generates more DSBs. Micronucleus formation also supported this conclusion. Low dose-rate γ-ray effects were also investigated. We first found that overexpression of hOGG1 also caused increased sensitivity to low dose rate γ-ray irradiation. The rate of micronucleus formation supported the notion that low dose rate irradiation increased genome instability.